Supporting or thwarting? The influence of European Union migration policies on African free movement regimes in West and North-Eastern Africa - Clare Castillejo; Eva Dick; Benjamin Schraven (Deutsches Institut für Entwicklungspolitik (DIE), 2019)
The European Union (EU) approach to migration in Africa has significantly shifted in the last few years. Notably since 2015, it has focused on preventing irregular migration and privileges engagement with the main countries of origin and transit of migrants. In the context of the 2015 Joint Valletta Action Plan (JVAP), a funding instrument - the EU Emergency Trust Fund for Africa (EUTF) -was created to channel development aid in support of EU interests in curbing migration. As reflected in historical and more recent policy agendas, economic integration and free movement within the continent and its regions constitute key elements of African development ambitions and narratives. But an increasing body of research suggests that EU activities (in particular the EUTF) sideline or even undermine African stakeholders and interests in decision-making and programming on migration. This paper analyses the effects of EU political dialogue and programming on regional free movement (RFM) in two African regions: the Intergovernmental Authority on Development (IGAD) in the Horn of Africa and the Economic Community of West African States (ECOWAS) in West Africa. These regions receive the greatest amount of EUTF funding. While both IGAD and ECOWAS have frameworks on RFM, these are at very different stages of development. The analysis, based on literature review and field research, shows that EU approaches to and impact on RFM differ significantly in the two regions. In the IGAD region, the EU is not undermining but rather supporting free movement - albeit not as significantly as it could. In contrast, in the ECOWAS region the EU's focus on preventing irregular migration is undermining progress on RFM. At least three factors drive this difference: 1) institutional coherence and decision-making powers vary considerably in the two regions; 2) whereas some powerful member states in the IGAD region consider free movement to be a barrier to their hegemonic role, member states in the ECOWAS region largely see it as positive; and 3) EU migration programming in these regions is driven by different levels of urgency - with the largest number of irregular migrants coming from West Africa, the EU's objective of curbing migration is more accentuated in the ECOWAS region. A number of policy processes between and within the EU and Africa are currently underway that could reshape how the EU engages with Africa on migration issues, provided existing tensions are acknowledged and addressed. Since RFM is in the long-term interests of both parties, given its potential value to contribute to growth, development and stability within Africa, the EU should pursue the following programmatic steps for its support: Supporting regional organisations. This includes tailored capacity support in strategic direction, analytical capacity and outreach to member states. This should build on lessons from existing EU projects in support of RFM. Enhancing coherence between security and development. This means for example that existing programmes addressing irregular migration are examined regarding their impact on free movement. Improving capacity of EU delegations. This requires linking the regional EU delegations more effectively to EU delegations in member states to support joint regional and national level actions on RFM.
Keywords: 330